2021
DOI: 10.3390/su131810187
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Irrigation Management Practices on Potato (Solanum tuberosum L.)

Abstract: Decisions in irrigation management can greatly impact the overall sustainability of potato production. A field study was conducted in 2018 and 2019 to evaluate the impacts of different irrigation regimes on yield and quality of three russet potato varieties. For Russet Burbank, fry quality at harvest and at 4 and 8 months after harvest was assessed. During early growth stages, the standard practice of irrigating to maintain 60–80% soil moisture was employed. The irrigation treatments were applied during the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…The field trial was conducted at the University of Wisconsin Hancock Agricultural Research Station (UW HARS) in Hancock, WI (latitude: 44°12.1413; longitude: 89°53.6840; 328 m asl) in 2020 and 2021. The soil texture was a Plainfield loamy fine sand (mixed, mesic Typic Udipsamment) (Crosby & Wang, 2021; Yuan et al., 2017). The soil organic matter content was lower than 1% in both years, as it consists of excessively drained coarse sand.…”
Section: Methodsmentioning
confidence: 99%
“…The field trial was conducted at the University of Wisconsin Hancock Agricultural Research Station (UW HARS) in Hancock, WI (latitude: 44°12.1413; longitude: 89°53.6840; 328 m asl) in 2020 and 2021. The soil texture was a Plainfield loamy fine sand (mixed, mesic Typic Udipsamment) (Crosby & Wang, 2021; Yuan et al., 2017). The soil organic matter content was lower than 1% in both years, as it consists of excessively drained coarse sand.…”
Section: Methodsmentioning
confidence: 99%
“…Al-Omran et al [49] also reported that the partial root-zone drying with 75% ETc did not result in significant yield loss as compared to full irrigation with 100% ETc. Crosby and Wang [50] also concluded that 25% deficit irrigation during late bulking and maturation stage could save significant irrigation water maintaining optimum tuber yield and quality, while over-irrigation with 125% ETc not being profitable compared to full irrigation in chipping potatoes. The varietal and seasonal differences in crop performance and tuber yield were also reported by Crosby and Wang [50].…”
Section: Tuber Yield and Yield Componentsmentioning
confidence: 99%
“…Crosby and Wang [50] also concluded that 25% deficit irrigation during late bulking and maturation stage could save significant irrigation water maintaining optimum tuber yield and quality, while over-irrigation with 125% ETc not being profitable compared to full irrigation in chipping potatoes. The varietal and seasonal differences in crop performance and tuber yield were also reported by Crosby and Wang [50]. The lower tuber yield in 2023 compared to 2022 could be due to extreme weather conditions, such as heat during the day and very cold temperatures at night.…”
Section: Tuber Yield and Yield Componentsmentioning
confidence: 99%